How Effective are School Years? Examining the Link Between Human Capital and Economic Growth in European Countries, 2014–2019 - Balog, Ilona Ida (Public Finance Quarterly, 2021)
This paper wishes to contribute to the examination of the relationship between human capital and economic growth. Human capital is measured by the average number of finished schooling years and its effect on economic growth is estimated on novel data in European countries. Data from the period between 2014 and 2019 show a negative coefficient for schooling years. In eastern countries in the analysis economic growth is generally higher than in Western-European countries. Economic growth in Hungary is higher than the estimated value explained by the analysed variables. The negative coefficient means that human capital measured by the number of schooling years does not accelerate economic growth any more, and further reforms of the education systems are needed in order to use human capital more efficiently.